Tanggung Jawab Hukum atas Penyalahgunaan Consent oleh Pelaku Telemarketing dalam Perspektif Undang-Undang Perlindungan Data Pribadi - Yaw, Tanidi; Y. B., Sandy Batara; Sampurna, Angelia; Utami , Lily Sri (Syntax Literate, 2025)
This study explores the legal responsibility for the misuse of consent by telemarketing actors under Law No. 27 of 2022 on Personal Data Protection (PDP Law). It specifically analyzes how consent is exploited in telemarketing practices and evaluates the extent to which the PDP Law provides a legal framework to address such violations. The law establishes both administrative and criminal sanctions against the misuse of personal data, including in the context of telemarketing. However, the enforcement of these sanctions faces significant challenges, such as limited institutional capacity, low public awareness of privacy rights, weaknesses in cyber law enforcement, and evidentiary difficulties in legal proceedings. To address these obstacles, the study proposes several measures: establishing an independent supervisory authority, enhancing public education and outreach, strengthening law enforcement capabilities, and fostering collaboration between government, private sector, and civil society. These efforts are expected to strengthen legal enforcement against consent violations and promote a safer, more trustworthy digital environment where individuals' personal data is effectively protected in telemarketing activities.